A Double Blind Immunohistological Study Of The Effect Of Topical Tretinoin On Photoaged Skin - Bose Sumit Kumar (Wolters Kluwer Medknow Publications, 1998)
Fifteen very fair women with mild to moderate photoaging in there 60â€s were tested by doubled blind immunohistological study. Tretinoin 0.05% cream applied daily was compared to its vehicle with regards to epidermal, basal, spinous differentiation markers and dendritic cells (Langerhanâ€s and melariocyte). In comparison with the control skin, tretinoin-treated skin showed the following changes: 1. From atrophy to normalization or hyperplasia of horny and prickle cell layers,2. Granular layer was normal to hypertrophied, 3. Basal cells were well-stained and thicker, 4. Basement membrane was thicker to normal in appearance and 5. Dendritic cells were increased in number (Langerhanâ€s). These results demonstrated a decelerating effect of tretinoin on the time clock of photoaging.